A nitrogen-containing all-solid-state hyperbranched polymer electrolyte for superior performance lithium batteries. Issue 12 (4th March 2019) - Zhang, Lei; Wang, Shi; Li, Jingyu; Liu, Xu; Chen, Pingping; Zhao, Tong; Zhang, Liaoyun
Abstract : A novel nitrogen-containing all-solid-state hyperbranched polymer electrolyte is first designed and prepared and shows superior performance. Abstract : Polyether-based materials, especially poly(ethylene oxide) (PEO) and derivatives thereof, have been extensively studied as Li-conducting all-solid-state polymer electrolytes (SPEs) for Li-based batteries due to their specific advantages such as easy fabrication, high safety, and outstanding compatibility with lithium salts. However, PEO-based polymers usually have too strong complexation ability with lithium ions and high crystallinity, resulting in a low lithium-ion transference number and room temperature ionic conductivity. In this study, we choose hyperbranched polyethylenimine (HPEI) as the core of a SPE matrix, while polyester segments as the arms through sequential ring-open polymerization (ROP) of glycolide (GC) and ε-caprolactone (CL). Specifically, the HPEI core containing N atoms can promote the dissociation of lithium salts, while the polyester segments can effectively dissolve lithium salts and transport ions. Furthermore, the SPE (HPEI–PGC–PCL/LiTFSI) is cast onto a ceramic film containing ceramic nanowires to prepare a composite SPE (CSPE), which can further construct ion transport channels at the interface of the polymer and nanowires. Synergizing the advantages of HPEI–PGC–PCL and ceramic nanowires, the CSPE exhibits superior electrochemical performance. Especially, the LiFePO4 /CSPE/Li cell exhibits a discharge capacity of 162 mA h g −1 at the C-rates of 0.2, 0.5 and 1C, and an average discharge capacity of 158 mA h g −1 with an average coulombic efficiency of 99.8% over 200 cycles at 0.5C. More importantly, the LiCoO2 /CSPE/Li cell also shows very good cycling performance (reaches 130 mA h g −1 at a current density of 0.06 mA cm −2 ) and rate capacity (reaches 80 mA h g −1 at a current density of 0.3 mA cm −2 ). This work highlights a new and novel host material that has the potential to be used as a high performance all-solid-state electrolyte for solid-state batteries.